Respostas

2014-04-05T16:09:29-03:00
3x²+4x+1=0
Δ=b² -4ac
Δ= (4)² - 4(3)(1)
Δ= 16 - 12
Δ=4

 \frac{-(4) +-  \sqrt{4} }{2(3)}
x' =  \frac{-4-2}{12}
x'=  \frac{-6}{12}
x'=- \frac{1}{2}

x"=  \frac{-4+2}{12} 
 \frac{-2}{12}
x" =  \frac{-1}{6}

1 5 1
n sei mecher nas ferramentas alguem me ajuda
  • Usuário do Brainly
2014-04-05T16:38:19-03:00
3x²+4x+1=0

a= 3    b= 4    c= 1

Δ=b²- 4*a*c
Δ=4²- 4*3*1
Δ=16-12
Δ=4    Δ= √4 =2

x= -b +- √Δ
     -------------
         2*a

x'= -4 +-2
     ----------
       2*3

x'= -4+2
     ----------
       6

x'= -2
     ----
      6

x''= -4-2
     -------
       6

x''= -6
     -----
       6

x''= -1